New mantras in corporate corridors : from ancient roots to global routes - Sharma, Subhash, 1951- (New Age International, 2007)
About the Book: This book is based on the idea of 'holistic globalization' rooted in a dynamic interaction between four fundamental forces of Market, State, Community and Self. This leads us to a new global ('viswa') vision of sacro-spiritual & sacro-civic society wherein there is a proper balance between economic development, social progress, and spiritual fulfillment. This vision envisages a new corporate model based on an integration of profit approach, social responsibility and good governance. In this context, Indian Management thought can make significant contributions to future development of management thought by opening new routes to global routes. The book presents a number of new management mantras, models and tools that enhance our understanding of management and social thought. These are based on 'integrative synthesis' of various intellectual traditions represented by three historical forces and processes viz. Western Enlightenment, Eastern Awakening and Many Routes to Nirvana. This synthesis is also represented by the metaphors of 'Western Windows', 'Eastern Doors' and 'Nirvana Corridors' that constitute the foundations of this book, leading us to new explorations of inter linkages between management thought, social discourse and spiritual concerns. Contents: PART-I- Social Setting & Ancient Text in New Context PART-II- Enlightened Leadership & Human Quality Development (HQD) PART-III- Strategic Gearing & Enterprise Performance Improvement Models PART-IV- Management Thought, Social Discourse & Spiritual Concerns: Toward New Corporate Awakening.